Drink in the Summer A Memoir of Croatia - Fabijančić, Tony (Our Lives: Diary, Memoir, and Letters, 2023)
Since childhood, Tony Fabijančić has travelled frequently to Yugoslavia and Croatia, the homeland of his father. He spent time with his peasant family in the village of Srebrnjak in the north and escaped to the Adriatic islands in the south where he could break free from the constraints of everyday life. Those two worlds-the north, marked by the haunting saga of family life, its history and material practices, and the south, a place defined by travel and escape-formed the two halves of Fabijančić's Croatian life. Over time, he observed Srebrnjak become a white-collar weekend retreat, the community of peasants of the 1970s, to which he was first introduced, only a distant memory. From the continental interior of green valleys and plum orchards to the austere and skeletal karst coast, Drink in the Summer is a unique record of a place and people now lost to time, a description of a country's varied landscapes, and a journey of discovery, freedom, beauty, and love.